Extended spectrum penicillins reduce the risk of omphalocele: A population-based case-control study - Raitio Arimatias; Tauriainen Asta; Leinonen Maarit K; Syvänen Johanna; Kemppainen Teemu; Löyttyniemi Eliisa; Sankilampi Ulla; Gissler Mika; Hyvärinen Anna; Helenius Ilkka (Elsevier, 2022)
Background: Omphalocele is a major congenital anomaly associated with significant morbidity and mortality. Regardless, the influence of maternal use of prescription drugs on the risk of omphalocele has only been addressed in a handful of studies. The aim of this study was to assess the influence of maternal risk factors and prescription drugs in early pregnancy on the risk of omphalocele.
Methods: We performed a nationwide register-based case-control study in Finland. The analysis is based on the Finnish Register of Congenital Malformations and Drugs and Pregnancy databases, both upheld by the Finnish Institute for Health and Welfare. All omphalocele cases were identified between Jan 1, 2004, and Dec 31, 2014. Five age-matched controls from the same geographical region were randomly selected for each case. The main outcome measures were maternal risk factors for omphalocele. Our analysis compared the maternal characteristics and the use of prescription drugs during the first trimester of pregnancy between case and control mothers.
Results: Mothers of 359 omphalocele cases were compared with 1738 randomly selected age and area-matched mothers of healthy infants between 1 January 2014 and 31 December 2014. Both maternal obesity (BMI ≥30) and diabetes increased the risk for omphalocele, and their co-occurrence accumulated this risk (aOR 5.06, 95% Cl 1.19-21.4). Similarly, history of multiple miscarriages was an independent risk factor (2.51, 1.16-5.43). The oral use of extended spectrum penicillins during the first trimester of pregnancy had a significant, protective influence (0.17, 0.04-0.71). These analyses were adjusted for sex, parity, and risk factors reported above. No significant changes in risk were observed with any other medication used during the first trimester.
Conclusion: In conclusion, these findings may suggest that extended spectrum penicillins in the first trimester reduces the risk of omphalocle formation. Additionally, consistent with earlier studies, previous repeated miscarriages, maternal obesity, and diabetes were significant risk factors for omphalocele.